Maize production under risk: The simultaneous adoption of off-farm income diversification and agricultural credit to manage risk - Shoaib Akhtar; Gu-cheng LI; Adnan Nazir; Amar Razzaq; Raza Ullah; Muhammad Faisal; Muhammad Asad Ur Rehman Naseer; Muhammad Haseeb Raza (Journal of Integrative Agriculture, 2019)
Farmers in Pakistan continue to produce maize under various types of risks and adopt several strategies to manage those risks. This study is the first attempt to investigate the factors affecting the concurrent adoption of off-farm income diversification and agricultural credit which the farmers use to manage the risk to maize production. We apply bivariate and multinomial probit approaches to the primary data collected from four districts of Punjab Province in Pakistan. The results show that strong correlations exist between the off-farm diversification and agricultural credit which indicates that the use of one risk management strategy leads to another. The findings demonstrate that education, livestock number, maize farming experience, perceptions of biological risks and risk-averse nature of the growers significantly encourage the adoption of diversification as a risk management tool while farm size inversely affects the adoption of diversification. Similarly, in the adoption equation of credit, maize farming experience, farm size, perceptions of price and biological risks and risk attitude of farmers significantly enhance the chances of adopting agricultural credit to manage farm risks. These findings are important for the relevant stakeholders who seek to offer carefully designed risk minimizing options to the maize farmers.